A pattern‐based approach to extract REA value models from business process models. Issue 1 (17th January 2017) - Boubaker, Anis; Leshob, Abderrahmane; Mili, Hafedh; Charif, Yasmine
Summary: Business models are economic models that describe the rationale of why organizations create and deliver value. These models focus on what organizations offer and why. Business process models capture business activities and the ways in which they are accomplished (i.e. their coordination). They explain who is involved in the activities, and how and when these activities should be performed. This paper discusses the alignment between business models and business process models. It proposes a novel systematic method for extracting a value chain (i.e. business model) expressed in the Resources, Events, Agents (REA) ontology from a business process model expressed in Business Process Model and Notation™. Our contribution is twofold: (1) from a theoretical standpoint we identified a set of structural and behavioural patterns that enable us to infer the corresponding REA value chain; (2) from a pragmatic perspective, our approach can be used to derive useful knowledge about the business process and serve as a starting point for business analysis.